Trend dan Faktor yang Berhubungan dengan Keberhasilan Pengobatan Pasien TB MDR Paduan Jangka Pendek di Indonesia 2017-2019 - Nenden Siti Aminah; Ratna Djuwita (Pro Health Jurnal Ilmiah Kesehatan, 2021)
TB problems in Indonesia are TB sensitive, Drug-Resistant TB and TB-HIV. TB-RO is the most challengging problem, the number of case finding is increase every year, but treatment rate is decrease. The use of short-term regiment since September 2017 is one of strategy to reduce default of TB treatment. This research was conducted to see trends and factors related to the TB treatment success rate among patients with Drug Resistance TB (TB RO) using Shorter Treatment Regiment (STR) in Indonesia 2017-2019. The study desain is restropective cohort. Data sources are all patients of TB RO using STR regiment, which is enrolled in the e-TB manager, Sud Directorate of Tuberculosis, MoH RI. The sampling method is total sampling that meets the inclusion and exclusion criteria. The analysis used was the chi-square test and the cox regression test. As many as 3,100 patients were included in the analysis, the trend of successful treatment of short-term mixed RO TB patients since 2017-2019 has continued to decline, with figures of 53.28%, 47.85% and 36.98%. The results of the analysis showed that factors related to treatment success were age, adherence, results of initial sputum examination of treatment, patterns of monoresistant and polyresistant resistance, and area of residence. Adherence is a dominant factor related to treatment success. Efforts should be made to strengthen compliance by conducting counseling as early as possible, PMO assistants from non-helath officers and initiating patient support groups in each MDR facility.